Sertifikasi atau Standarisasi Khatib? Respons Para Da’i di Kota Mataram - Fahrurrozi, Fahrurrozi (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2018)
This study discusses the response of da'i in the city of Mataram related to the discourse on certification of Friday prayer preachers which was commissioned by the government in 2017. This study used qualitative methods. In-depth interview towards da'i and Jumat prayer preachers was utilized to collect the data to answer the focus of the research. The findings of this study revealed that currently the khatib certification is not necessary. This is because there is no strong evidence that has shown the radicalization occurs in Mataram resulted from Friday sermon. However, the respondents emphasized the importance of standardization of all aspects of religion, especially on aspects of the mosque management and religious institutional management under the guidance of the Indonesian Ministry of Religion and Islamic community organizations.